2018
DOI: 10.1111/nuf.12289
|View full text |Cite
|
Sign up to set email alerts
|

Exploring, defining, and illustrating a concept: Structural and psychological empowerment in the workplace

Abstract: Aim The aim of this concept analysis is to clarify the meaning and relationship of psychological and structural empowerment. Background Empowerment is linked to positive organizational and individual constructs and outcomes. Improving the work environment may assist in sustaining a fragile and essential workforce. Design Walker and Avant’s method was used to guide an analysis of this concept. Data Source Resources published from 1970 to 2018 were identified via electronic databases, empirical works, and modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(87 reference statements)
0
18
0
1
Order By: Relevance
“…Finally, impact is the sense of ability to influence important work outcomes (Avolio et al, 2004). Various studies have shown that high psychological empowerment level is associated with low stress, burnout and turnover intention, and high organizational commitment and job satisfaction (Abel & Hand, 2018;Ibrahem, Elhoseeny, & Mahmoud, 2013;Ouyang, Zhou, & Qu, 2015;Oyeleye, Hanson, O'Connor, & Dunn, 2013). The Psychological Empowerment Scale is a 12-item scale measuring the four constructs competence (e.g., 'I am confident about my ability to do my job'), impact (e.g., 'My impact on what happens in my department is large'), meaning (e.g., 'The work I do is very important to me'), and self-determination (e.g., 'I can decide on my own how to go about doing my work') (Spreitzer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, impact is the sense of ability to influence important work outcomes (Avolio et al, 2004). Various studies have shown that high psychological empowerment level is associated with low stress, burnout and turnover intention, and high organizational commitment and job satisfaction (Abel & Hand, 2018;Ibrahem, Elhoseeny, & Mahmoud, 2013;Ouyang, Zhou, & Qu, 2015;Oyeleye, Hanson, O'Connor, & Dunn, 2013). The Psychological Empowerment Scale is a 12-item scale measuring the four constructs competence (e.g., 'I am confident about my ability to do my job'), impact (e.g., 'My impact on what happens in my department is large'), meaning (e.g., 'The work I do is very important to me'), and self-determination (e.g., 'I can decide on my own how to go about doing my work') (Spreitzer, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Empowerment is a multi-faceted construct, in whose psychological understanding the emphasis was put on active orientation to a work role expressed in four cognitions: Meaning, competence, self-determination, and impact [50]. These qualities are still crucial and are applied in research; however, as noted by Abel and Hand [45], the content of this concept is ambiguous, and some difficulties exist in its translation into other languages. On the other hand, the aforementioned authors refer directly to the publications of Conger and Kanugo [49] and Spreitzer's [51,52] research.…”
Section: An Individual Seen As An Agentmentioning
confidence: 99%
“…One recent concept analysis melded structural and psychological empowerment together, identifying attributes of shared decision‐making, motivational disposition, growth, access, influence, power or control, and options . While these elements capture many of the essential components from the literature, the focus is exclusively on an individual being granted the ability to grow or increase capacity within an organizational role or career trajectory.…”
Section: Empowermentmentioning
confidence: 99%
“…Several individual factors have been correlated with or shown to impact empowerment, including certification, sense of meaning, recognition, competence, and choice . In their concept analysis, Abel and Hand report organizational antecedents as access to opportunities, resources, knowledge, support, guidance, and feedback. Pulling out elements that focus on an individual apart from the context of the workplace, we can identify a sense of meaning and opportunities as important antecedents to individual nurse empowerment.…”
Section: Empowermentmentioning
confidence: 99%